Ethnic Language Maintenance Among The Maanyan Emigrants In Indonesia - Kumpiady Widen (FKIP, Universitas Palangka Raya, 2025)
Some of the Maanyans or the Dayak Maanyan as one of the indigenous ethnic groups in Central Kalimantan Province have emigrated from their second original native land, East Barito Regency, Central Kalimantan. They emigrated to other parts of Central Kalimantan or any other parts of Indonesia. Their basic purposes for leaving their second original native land are to look for jobs as well as to study. At their new settlement, some of the Maanyan emigrants still strongly maintain their native language by inheriting the language to their children while some others think that it is not necessary. Among the factors influencing the ethnic language maintenance among the Maanyan emigrants are ethnic identity, the attitudes of the parents, intra-and inter-ethnic group communication, the need for telling or saying something secret, the establishment of Dusmala in a number of capital cities, and the Indonesian government policy on ethnic language maintenance.